Optimizing batch distillation parameters for enhanced bioethanol purification from fermentation - Ni Ketut Sari; Reva Edra Nugraha; Dira Ernawati; Komang Nickita Sari; Wahyu Dwi Lestari; Mohammad Tauviqirrahman; Muhammad Imam Ammarullah (Green Chemistry Letters and Reviews)
This study aims to improve the purity of bioethanol produced from Bioethanol Recycle of Enzyme Fermentation (BR-EF) by employing batch distillation and absorption techniques. A distillation column with raschig rings and molecular sieve was used, with an initial BR-EF volume of 1 L and concentrations ranging from 15% to 35% (v/v). The distillation process, conducted at 78°C using microwave heating, lasted between 2–6 h. The optimal bioethanol concentration of 97.72% (v/v) was achieved with a 30% (v/v) BR-EF concentration and a 4-hour distillation time. Optimal response with a bioethanol concentration of 99.824% (v/v). The ideal conditions for Multiple Response Prediction were determined to be flow rate of adsorption and weight of silica gel are 0.116 and 58.295. Further optimization was performed using MATLAB (Matrix Laboratory) and Differential Expert (DE) to assess the impact of BR-EF concentration and distillation time on bioethanol yield, with results visualized in a 3D response surface graph. This study offers valuable insights into optimizing bioethanol production, enhancing its purity and market potential.